Impact evaluation of the strengthen PSNP4 institutions and resilience (SPIR) development food security activity (DFSA): Midline report - Alderman, Harold; Gilligan, Daniel O.; Hidrobo, Melissa; Leight, Jessica; Ramani, Gayathri V.; Taffesse, Alemayehu Seyoum; Tambet, Heleene (2020)
The Strengthen PSNP4 Institutions and Resilience (SPIR) Development Food Security Activity (DFSA) in Ethiopia is a five-year project (2016-2021) supporting implementation of the fourth phase of the Productive Safety Net Programme (PSNP4) as well as providing complementary livelihood, nutrition, gender and climate resilience activities to strengthen the program and expand its impacts. The main objectives of SPIR are to enhance resilience to shocks and livelihoods and improve food security and nutrition for rural households vulnerable to food insecurity. Activities under SPIR are organized into four Purposes: 1) livelihoods, 2) nutrition, 3) women’s and youth empowerment, and 4) climate resilience. In each of these Purposes, SPIR provides community-level programming, training of government staff involved in public service delivery at the woreda (district) and kebele (subdistrict) level, and targeted livelihood transfers. IFPRI is conducting an experimental, quantitative impact evaluation of SPIR designed to measure the causal impact of multisectoral “graduation model” packages of livelihoods, nutrition, gender equity and mental health interventions for improving outcomes in several domains, including livelihoods, food security, child nutrition, women’s empowerment, mental health and intimate partner violence (IPV). The impact evaluation uses a clustered randomized controlled trial (RCT) design with four intervention arms (three treatments and a control group) to test the relative effectiveness of these packages of interventions to improve outcomes for PSNP4 beneficiaries. This midline report of the impact evaluation presents evidence from the first 15 months of the project on program performance and the effectiveness of delivery. The midline survey was conducted from July 25 to October 23, 2019 during which time a total of 3,968 households were interviewed out of the target of 4,082 households for the entire study sample.